2018
DOI: 10.1371/journal.pone.0190646
|View full text |Cite
|
Sign up to set email alerts
|

Examination of China’s performance and thematic evolution in quantum cryptography research using quantitative and computational techniques

Abstract: This study performed two phases of analysis to shed light on the performance and thematic evolution of China’s quantum cryptography (QC) research. First, large-scale research publication metadata derived from QC research published from 2001–2017 was used to examine the research performance of China relative to that of global peers using established quantitative and qualitative measures. Second, this study identified the thematic evolution of China’s QC research using co-word cluster network analysis, a computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…The USA shows a much smaller contribution to QT 2.0 than could be expected from their otherwise leading role in science. China has a far overproportionate contribution, especially in the field of Q COMM-corroborated by its hub-like function in the topical map and confirming the findings of Olijnyk [64]. Germany can be found on the third rank of contributors with a much higher than expected share of QT 2.0 publications.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The USA shows a much smaller contribution to QT 2.0 than could be expected from their otherwise leading role in science. China has a far overproportionate contribution, especially in the field of Q COMM-corroborated by its hub-like function in the topical map and confirming the findings of Olijnyk [64]. Germany can be found on the third rank of contributors with a much higher than expected share of QT 2.0 publications.…”
Section: Discussionsupporting
confidence: 72%
“…The authors were interested in the internal team structure, collaborations, and prospective development. Olijnyk [64] was interested in China's involvement in the area of quantum cryptography between 2001 and 2017 and witnessed China taking on a leading role. Dhawan et al [65] focused on the global publication output in quantum computing research between 2007 and 2016 and reported results concerning the top contributing countries very similar to ours (see Section 5.…”
Section: Quantum Technology 20: Foci Of Research In Four Subfieldsmentioning
confidence: 99%
“…They concluded that funding defensed-based research for universities decreases regional entrepreneurship activities in the short-term, however is positively related to entrepreneurship in the long-term. Together with other studies about spill-over effects from military to civilian innovations and research (Acosta, Coronado, Marín, & Prats, 2013;Kas et al, 2012;Olijnyk, 2018), these findings indicate that defense-related funding impacts the way scientific research is conducted and the development of technological innovations.…”
Section: Us National Security Funding For Research Innovationssupporting
confidence: 61%
“…With the growing interest in the QIST, there are several works to perform quantitative analyses on the state of the art of the QIST [9,10,11,12,13,14,15,16]. These works clarified that i) the number of publications in the QIST is rapidly growing, ii) the leading countries of the QIST research are the US and China, and iii) Institutions in Europe have more collaborative works than those in the other countries.…”
Section: Introductionmentioning
confidence: 99%
“…These works clarified that i) the number of publications in the QIST is rapidly growing, ii) the leading countries of the QIST research are the US and China, and iii) Institutions in Europe have more collaborative works than those in the other countries. In addition to these, more specific analyses have been conducted in quantum cryptography [10] and quantum machine learning [14]. The collaboration network in quantum information authors is found to be a small-world network [16].…”
Section: Introductionmentioning
confidence: 99%